Analisis Efisiensi Penggunaan Dana Masyarakat Uuntuk Kegiatan Dharma Pendidikan Di Institut Pertanian Bogor - Mohammad Nur Hadi; Hermanto Siregar; Hendro Sasongko (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
This study focuses on measuring the efficiency of all departments in Bogor Agricultural Institute using Data Envelopment Analysis (DEA) on the first stage and the second stage is to determine the factors that influence the efficiency. DEA methodology is to evaluate the efficiency by comparing all departments and using financial as inputs and non-financial factors as an output. The second stage analysis uses Tobit regression because dependent factors are censored between 0 to1 and independent factors uncensored. The results of the first stage demonstrate that 54.29% of departments in Bogor Agricultural University is efficiently operated in terms of academic factors during the period from 2012 to 2014, while 45.71% is inefficient. And for the second stage, the result is international accreditation and non-academic staff are the factors that can influence the efficiency of departements.